2020
DOI: 10.1111/1751-7915.13719
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient conditions determine the localization of Bacillus thuringiensis Vip3Aa protein in the mother cell compartment

Abstract: Vip3Aa was first identified as a protein secreted during the vegetative growth phase of Bacillus thuringiensis (Bt) bacteria and which shows high insecticidal toxicity against lepidopteran insect pests (Estruch et al., 1996). Bt strains formulated as bio-insecticides only had low amounts of Vip3Aa secreted to the medium. Here, we report that Vip3Aa proteins produced by three different Bt strains, including an industrial strain, were indeed not secreted to the culture solution when grown in sporulation medium, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Therefore, we assume that the results we describe in this study should be valid for all these B. thuringiensis strains. This claim agrees with a result showing that in B. thuringiensis strain KN11, Vip3A is specifically produced during the stationary phase and accumulates in the cytoplasm of bacteria grown in twofold diluted LB medium (35). The production of Vip3A during vegetative growth (12) and the weak vip3A expression we observed during the exponential growth phase (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we assume that the results we describe in this study should be valid for all these B. thuringiensis strains. This claim agrees with a result showing that in B. thuringiensis strain KN11, Vip3A is specifically produced during the stationary phase and accumulates in the cytoplasm of bacteria grown in twofold diluted LB medium (35). The production of Vip3A during vegetative growth (12) and the weak vip3A expression we observed during the exponential growth phase (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we assume that the results we describe in this study should be valid for all these B. thuringiensis strains. This claim agrees with a result showing that in B. thuringiensis strain KN11, Vip3A is produced specifically during the stationary phase and accumulates in the cytoplasm of bacteria grown in 2-fold-diluted LB medium ( 35 ). The production of Vip3A during vegetative growth ( 12 ) and the weak vip3A expression we observed during the exponential growth phase ( Fig.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, Wang et al [ 30 ] reported that Vip3Aa secretion is nutrient-dependent. When grown in a sporulation medium, Vip3Aa were not secreted to the culture solution but were retained in the mother cell compartment.…”
Section: Discussionmentioning
confidence: 99%